FAKTOR – FAKTOR YANG MEMPENGARUHI EKSPOR ALAS KAKI INDONESIA KE EROPA TAHUN 2005 – 2014 - Dhimas Fajar Prasetyo fajar prasetyo; Syapsan Syapsan; Ando fahda aulia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aim to invest the factors that influence the export of Indonesian footwear to Europe useing multiple regression analysis method. This research used secondary data from Central Burea of statistic, World Bank, Bank of Indonesian. This research to know the effect of footwear price, Rupiah’s exchange rate to America’s Dollar, GDP Uni Europe, production value to footwear export Indonesian to Europe. The results of the research that are simultaneously variables of international price, the rupiah’s exchange rate to us Dollar, Gross Domestic Product (GDP) and production value significantly influence the export of footwear Indonesia to Europe from 2005 to 2014. Partially, GDP and production has a significant positive effect to footwear export to Europe, and Rupiah’s exchange rate has a significant negative effect to the above export. Another variable, international price is not significantly influence the Indonesian footwear export to Europe. The magnitude of the effect caused by four’s R2 is a compact variable to the dependent variable is 95,4 % while the remaining 4,6 % are influenced by variable other variables that are not researched in this study. Keywords : Export, International price,the rupiah’s exchange rate, Gross Domestic Product (GDP), Production value